A Stronger Doctrine of Double Effect. Issue 4 (2nd October 2018) - Bronner, Ben; Goldstein, Simon
ABSTRACT: Many believe that intended harms are more difficult to justify than are harms that result as a foreseen side effect of one's conduct. We describe cases of harming in which the harm is not intended, yet the harmful act nevertheless runs afoul of the intuitive moral constraint that governs intended harms. We note that these cases provide new and improved counterexamples to the so-called Simple View, according to which intentionally phi -ing requires intending to phi . We then give a new theory of the moral relevance of intention. This theory yields the traditional constraint on intending harm as a special case, along with several stronger demands.